IMPLEMENTING OF STRUCTURAL ANALYTICAL SYNTHETIC (SAS) METHODS TO IMPROVE THE ABILITY OF EARLY READING OF ELEMENTARY SCHOOL STUDENTS - Hermita, Neni; Astri Widyanthi; Kurniaman, Otang; Gustimal Witri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This research is motivated by the problem of the low ability to read at the beginning among students, so the SAS method is applied to help students succeed in initial reading. The purpose of this study was to determine the differences in pretest and posttest scores by applying Structural Analytical Synthetic (SAS) in the initial reading of elementary school students and to determine the increase from pretest to posttest. This type of research is a pre-experimental study with a pretest-posttest one group design, which is an experiment carried out in only one group without comparison. This study was conducted in class 1 with 34 students. Based on the results of the study, it was found that the average reading ability before treatment (pretest) was 51.77, while the average reading ability after treatment (posttest) was 88.41, and the average value of gain normality was 0.76, which is categorized as high. The results of hypothesis testing using the t-test with tcount = 51.080 and ttable = 2.0345 can be concluded that tcount > ttable, thus rejecting H0, which means significant. This indicates that there is a significant increase in initial reading ability in class I students between before (pretest) and after (posttest) applying the Structural Analytical Synthetic (SAS) method.